A promising 1D Cd-based hybrid perovskite-type for white-light emission with high-color-rendering index. Issue 52 (23rd November 2022) - Gassara, Mahdi; Msalmi, Rawia; Liu, Xinghui; Hassen, Fredj; Moliterni, Anna; Ben Hamadi, Naoufel; Guesmi, Ahlem; Khezami, Lotfi; Soltani, Taoufik; Naïli, Houcine
Abstract : The synthesized 1D-perovskite-type (C6 H7 NBr)3 [CdBr5 ] shows a broad-band white light emission with an extra-high CRI of 98 and chromaticity coordinates (0.30, 0.32). Abstract : A one dimensional (1D) perovskite-type (C6 H7 NBr)3 [CdBr5 ] (abbreviated 4-BAPC) was synthesized by slow evaporation at room temperature (RT). 4-BAPC crystalizes in the monoclinic system with the space group P 21 / c . The 1D inorganic chains are formed by corner sharing CdBr6 octahedra. Thermal measurement shows that 4-BAPC is stable up to 190 °C. Optical characterization demonstrates that the grown crystal is an indirect bandgap material with a bandgap value of 3.93 eV, which is consistent with theoretical calculations. The electronic structure, calculated using density functional theory, reveals that the valence band originates from a combination of Br-4p orbitals and Cd-4d orbitals, whereas the conduction band originates from the Cd-5s orbitals. The photoluminescence spectroscopy shows that the obtained material exhibits a broad-band white light emission with extra-high CRI of 98 under λ exc = 380 nm. This emission is mainly resulting from the self-trapped exciton recombinations within the inorganic CdBr6 octahedron, and the fluorescence within the organic conjugated ammonium salt.